Nowcasting quarterly GDP dynamics in the euro area: The role of sentiment indicators - Paweł Gajewski (Comparative Economic Research. Central and Eastern Europe, 2014)
The paper compares the most closely watched sentiment indicators with respect to their ability to nowcast quarterly GDP dynamics in the Euro Area and its biggest economies. We analyse cross-correlations and out-of-sample forecast errors generated from equations estimated by rolling regressions in fixed-length window. The results show that models employing PMI Composite perform best in the cases of the Euro Area, Germany, France and Italy, whilst Spanish GDP dynamics is best nowcasted using ESI-based models. PMI-based models generate the most accurate nowcasts at the beginning of the quarter, as well as during periods of high volatility of GDP growth rates
Keywords: 330; nowcasting; sentiment indicators